A globally distributed mobile genetic element inhibits natural transformation of Vibrio cholerae - Dalia, Ankur B. (Proc Natl Acad Sci U S A, 2015)
Natural transformation is one mechanism of horizontal gene transfer (HGT) in Vibrio cholerae, the causative agent of cholera. Recently, it was found that V. cholerae isolates from the Haiti outbreak were poorly transformed by this mechanism. Here, we show that an integrating conjugative element (ICE)-encoded DNase, which we name IdeA, is necessary and sufficient for inhibiting natural transformation of Haiti outbreak strains. We demonstrate that IdeA inhibits this mechanism of HGT in cis via DNA endonuclease activity that is localized to the periplasm. Furthermore, we show that natural transformation between cholera strains in a relevant environmental context is inhibited by IdeA. The ICE encoding IdeA is globally distributed. Therefore, we analyzed the prevalence and role for this ICE in limiting natural transformation of isolates from Bangladesh collected between 2001 and 2011. We found that IdeA(+) ICEs were nearly ubiquitous in isolates from 2001 to 2005; however, their prevalence decreased to ∼40% from 2006 to 2011. Thus, IdeA(+) ICEs may have limited the role of natural transformation in V. cholerae. However, the rise in prevalence of strains lacking IdeA may now increase the role of this conserved mechanism of HGT in the evolution of this pathogen.